Study of the Inhibitive Kinetic Spectrophotometry of Protein-Arsenazo III-Potassium Periodate - Li, Jing-Mei; Shi, Wei; Zhai*, Qing-Zhou (Asian Journal of Chemistry, 2011)
Quantitative determination of protein is an important parameter and indicator of other nature and function investigation of proteins. A novel kinetic spectrophotometric method for the determination of protein is proposed based on the inhibitive effect of bovine serum albumin (BSA) on the oxidation reaction of arsenazo III (ASA III) by potassium periodate in the medium of the Clark-Lubs of pH 3.0. The maximum absorption peak of BSA-ASA III-KIO4 system locates at 552 nm. The absorbance difference (DA) is linearly related with the concentration of bovine serum albumin over the range of 8-60 μg mL-1 and fitted the equation: DA = 9.832 × 10-3 C (C: μg mL-1)- 0.0797, with a correlation coefficient g = 0.9932. The detection limit of the method was 4.8 μg mL-1. The method was successfully used to determine protein content in milk, soybean milk, soybean powder and egg white samples, with relative standard deviations of less than 5 % for 13 replicate determinations. The recovery of the method was 100.7-103.7 %.